2009
DOI: 10.1159/000219434
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin Combined with Continuous Infusion of 5-Fluorouracil as First-Line Chemotherapy in Patients with Metastatic or Recurrent Gastric Adenocarcinoma

Abstract: Background: The aim of this clinical study was to evaluate the efficacy of combination chemotherapy of oxaliplatin, leucovorin and continuous-infusion 5-fluorouracil (5-FU) for advanced gastric cancer. Methods: Patients with previously untreated gastric cancer with measurable disease received oxaliplatin (100 mg/m2, day 1), followed by leucovorin (100 mg/m2, day 1) and 5-FU (2,400 mg/m2, days 1–2), which was repeated every 2 weeks. The primary endpoint was overall response rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Moreover, as the liver was the major target organ for acute cadmium exposure, and metallothionein expression was lower in hepatomas than that in normal liver tissues, such characteristics made it possible to develop cadmium as a potential antihepatoma drug. Nowadays, the combined treatment is proven to be beneficial in lowering the administered dosage of chemotherapeutic drugs while maintaining or even enhancing the antitumor effects [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as the liver was the major target organ for acute cadmium exposure, and metallothionein expression was lower in hepatomas than that in normal liver tissues, such characteristics made it possible to develop cadmium as a potential antihepatoma drug. Nowadays, the combined treatment is proven to be beneficial in lowering the administered dosage of chemotherapeutic drugs while maintaining or even enhancing the antitumor effects [25]. …”
Section: Discussionmentioning
confidence: 99%
“…No consensus has yet been reached regarding an optimal follow-up schedule and no study has shown a survival benefit for any particular follow-up program over another [22,23,24]. However, new chemotherapeutic agents, such as taxane, irinotecan, oxaliplatin, a new oral fluoropyrimidine, and targeted agents, are expected to provide effective treatment options for recurrences detected early [25,26,27,28]. A large prospective randomized controlled clinical trial is needed to verify the advantages of intensive follow-up program and new therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…The adducts of oxaliplatin appear to be more effective than cisplatin adducts with regard to the inhibition of DNA synthesis. In published phase II trials, the oxaliplatin-based regimens demonstrated a response rate ranging from 40 to 50% in chemotherapy-naive AGC patients [9,10,11]. Also, oxaliplatin/5-FU/leucovorin combinations have proved to be active and tolerable in elderly AGC patients [12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%